Collaborative Translation in the Digital Age - Tsai, Yvonne (Research in Language, 2020)
This study investigates the learning experiences of student translators participating in collaborative translation with and without the use of translation technology through collaborative translation teaching and practical exercises. The effectiveness and efficiency of two types of collaboration (face-to-face and virtual) are surveyed in terms of students’ cooperation and communication, the effort they invest into translation exercises, the importance they attach to these exercises, and the effectiveness of translation technology in collaborative translation. We use questionnaires to obtain a comprehensive overview of the translation process of and feedback on collaborative translation from student translators. Face-to-face and virtual collaborative translations are performed in English–Chinese translation courses to compare the learning effectiveness of virtual and face-to-face collaboration, enhance our understanding of how collaborative translation facilitates reciprocity, and offer recommendations to enhance translation teaching. This study develops collaborative translation teaching methods and designs collaborative translation curricula. Exploring the core criteria of collaboration, effectiveness, and efficiency through the reports of student translators collaborating face-to-face and online will contribute to the establishment of a collaborative translation framework.